PENGEMBANGAN MEDIA VIDEO PRAKTIKUM MENGGUNAKAN APLIKASI CANVA PADA MATA KULIAH FISIOLOGI TUMBUHAN UNTUK MAHASISWA PENDIDIKAN BIOLOGI SEMESTER V FKIP UNIVERSITAS PASIR PENGARAIAN - Meirina Brahmana, Eti; Febriani; Mubarrak, Jismi; Lestari, Rena; Dahlia, Dahlia (Jurnal Edu Research, 2024)
This study aims to determine the feasibility of plant physiology practicum video media for fifth semester biology students at FKIP of University of Pasir Pengaraian . This research was carried out from March to July 2023. The type of research used was the Brog and Gall Research and Development model. The population in this study were fifth semester students of the Biology Education Study Program class of 2021. Data was collected using a questionnaire and data were analyzed descriptively. The results showed that the plant physiology practicum video media for biology students in semester V as a whole was declared "decent" with an average percentage of 75,98%. Based on the validation of linguists with an average acquisition of 82,85% including the "very appropriate" category, validation of media experts with an average acquisition of 85,33% including the "very feasible" category, and validation of material experts with an average acquisition of 62,66% including the "decent" category, individual trials with an average acquisition of 67,11% included in the "adequate" category, small group trials with an average acquisition percentage of 75.22% included in the "adequate" category, and field trials with the average percentage gain of 82.94% is included in the "very decent" category. So the results of this study indicate that the video media for plant physiology practicum is suitable for use by educators and students in the learning process.